1994
DOI: 10.1161/01.res.75.6.1064
|View full text |Cite
|
Sign up to set email alerts
|

des-Arg9-bradykinin produces tone-dependent kinin B1 receptor-mediated responses in the pulmonary vascular bed.

Abstract: Responses to des-Arg'-bradykinin, a selective kinin Bi receptor agonist, were characterized in the pulmonary vascular bed of the intact-chest cat. Injections of des-Arg'-bradykinin into the perfused lobar artery under low-resting tone conditions caused dose-related increases in lobar arterial pressure; whereas in the same experiment under elevated tone responses under elevated-tone conditions were inhibited by N'-nitro-L-arginine methyl ester, suggesting that des-Arg'-bradykinin stimulates the release of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…26 The present study, using lisinopril, demonstrates a similar result in association with an increased CD response to bradykinin. However, lisinopril did not modify the coronary responses to des-Arg 9 -bradykinin, which is in accordance with observa- tions in the pulmonary circulation of cats, 10 indicating that in the coronary circulation in vivo, ACE plays only a small role in des-Arg 9 -[Leu 8 ]-bradykinin metabolism. Although it has been shown in vitro that ACE inhibitors may prevent the degradation of des-Arg 9 -bradykinin, 27 an in vivo experiment did not find an increased blood concentration of des-Arg 9 -bradykinin after enalapril administration.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…26 The present study, using lisinopril, demonstrates a similar result in association with an increased CD response to bradykinin. However, lisinopril did not modify the coronary responses to des-Arg 9 -bradykinin, which is in accordance with observa- tions in the pulmonary circulation of cats, 10 indicating that in the coronary circulation in vivo, ACE plays only a small role in des-Arg 9 -[Leu 8 ]-bradykinin metabolism. Although it has been shown in vitro that ACE inhibitors may prevent the degradation of des-Arg 9 -bradykinin, 27 an in vivo experiment did not find an increased blood concentration of des-Arg 9 -bradykinin after enalapril administration.…”
Section: Discussionsupporting
confidence: 86%
“…11 In cats, the pulmonary vascular bed contains functional B 1 receptors; the stimulation of these receptors produces tone-dependent changes in pulmonary artery pressure. 10 In dogs, B 1 receptors are also present in the isolated renal artery and mediate vasorelaxation, 12 and in intact preparations, B 1 receptor stimulation by des-Arg 9 -bradykinin produces a hypotensive effect. 13,14 By use of a specific antibody directed to the peptide sequences of B 1 receptors, it has recently been shown in humans that B 1 receptors are present not only in vascular endothelial and smooth muscle cells of large elastic arteries but also in muscular arteries, such as coronary arteries and muscular arterioles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, B 1 receptors exhibit high anities for kinin metabolites such as des-Arg 9 -BK and des-Arg 9 -kallidin, and are selectively antagonized by desArg 9 , [Leu 8 ]-BK and des-Arg 9 , [Leu 8 ]-kallidin. The constitutive expression of B 1 receptors is limited to certain types of tissues, such as dog coronary vessels (Nakhostine et al, 1993) and cat pulmonary vascular bed (DeWitt et al, 1994). B 1 receptors are also unique in that they can be up-regulated during certain pathophysiological situations, and a de novo synthesis of B 1 receptors occurs during in vitro incubation (Bouthillier et al, 1987;.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the B1 receptor induces relaxation or contraction of various smooth muscle cell preparations, mediates chronic pain, and may be involved in chronic inflammation (1). Recent studies have demonstrated the expression of the B1 receptor in apparently healthy renal (13), intestinal (14), ocular (15), stomach (16), and pulmonary (17) tissues; however, the role of the B1 receptor in homeostasis and wound repair is not understood. Activation of the B1 receptor stimulates prostaglandin synthesis in fibroblasts, release of tumor necrosis factor ␣ and interleukin-1␤ from macrophages, and prostaglandin and platelet-activating factor synthesis in endothelial cells (1).…”
mentioning
confidence: 99%